The Influence of Board Independence, Financial Expertise, and Gender on Financial Distress of SOEs and Infrastructure in Indonesia - Hidayatullah, Angga Guidanto (Dinasti Publisher, 2026)
The high risk of financial distress among state-owned enterprises in the infrastructure sector is primarily driven by the heavy financial burden of national strategic projects. This study focuses on examining how the characteristics of the board of commissioners influence the financial stability of companies facing financial pressure. The objective of this research is to analyze the effect of board independence, board expertise, and gender diversity on the level of financial distress. This study employs a quantitative method using panel data regression on infrastructure state-owned enterprises listed on the IDX during the period 2014 to 2023. The results show that board independence has a negative and significant effect on financial distress as measured by the Z Score and F Score models, no significant effect in the M Score model. Board expertise does not significantly affect financial distress in the Z Score and F Score models, but has a positive and significant effect in the M Score model. Gender diversity on the board does not show a significant impact in any of the three models. Findings suggest that the corporate governance mechanism, particularly through the independence, expertise, and diversity of the board of commissioners, can support more effective supervision and strategic decision-making.